An examination of the Relationship Between Stock Return and Financial Ratios : Empirical Evidence From Tehran Stock Exchange - Kalhorpour, Elham (2010)
This study examines the relationship between stock returns and financial ratios, namely, return on equity, return on sales, earnings per share, current ratio, cash ratio, asset turnover, and equity multiplier, in the Tehran Stock exchange from 2004 to 2009.